Influencia del programa de fábulas en la mejora de la comprensión lectora de los niños de 4 años del C.E.E “Rafael Narváez Cadenillas” de la ciudad de Trujillo en el 2017 - Ibañez Huamán, Andrea Dolybeth (2018)
The purpose of this research is to make known the improvement of reading comprehension through the program of fables in children of 4 years of the C.E.E "Rafael Narváez Cadenillas" of the city of Trujillo of the year 2017 " The research was applied and a quasi-experimental design was used with experimental group and control group with pretest and posttest. The experimental group consisted of 18 children, 7 girls and 11 boys, 4 years old, who participated in the program of fables in relation to reading comprehension, using the facilities of C.E.E "Rafael Narváez Cadenillas". The results of the pretest show that the children subject of research presented an average score of 10.5 (38.87%) in reading comprehension. After the application of the fables program, the children of the experimental group were able to improve significantly in an average score of 20.16 (75.12%) their reading comprehension. Through this research, the following conclusions were reached: The children of the experimental group according to the post-test result managed to significantly improve their reading comprehension, as evidenced by the total average score of 20.16 (75. 21%). The children of the control group according to the results of the posttest managed to improve their reading comprehension very lightly, as evidenced by the total average score of 10.66 (39.50%)